Itineraries of power : texts and traversals in Heian and medieval Japan - Kawashima, Terry (Harvard East Asian monographs, 2016)
""Examines a selection of prose narratives and poetry of the mid-Heian to medieval eras (900-1400) which conspicuously features tropes of movement. Argues that the concurrent appearance in a story of a character's physical motion and the techniques identified with literary strategies of motion is a textual signpost urging readers to focus on how the work conceptualizes relations of power and claims to authority"--